GROWTH OF MANGROVE COCKLE (Anandara antiquata) CULTURED IN CAGES - Pattikawa, Jesaja A.; Ferdinandus, Elizabeth (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2009)
Study on growth of mangrove cockle (Anadara antiquata) was conducted in the intertidal area of Passo, Inner Ambon Bay. Three size-classes of 25 individual cockles were cultured in 1 m3 cage. Length increment data was collected every two weeks for seven periods of observation. Relative growth rate, length-weight relationship and condition factor were estimated using formula proposed by Effendie, Pauly and King, respectively. The results showed that the small size had the highest length increment and relative growth rates while the large size had the best condition factor. Length-weight relationship showed isometric growth for all categories.